Ruang Terbuka Hijau di Kelurahan Banta-Bantaeng Kecamatan Rappocini Kota Makassar - Nashrah Arsyad (LOSARI : Jurnal Arsitektur Kota dan Pemukiman, 2016)
Public Open Space is part of the city's sub-system. The narrow conditions and scarcity of urban space that are widely encountered in various big cities today often marginalize the existence of public open spaces. As a result, there is an imbalance in synergy, proportion, ratio, distribution (spread) of public open space in the city. The availability of open space in an area has a very significant role in shaping the mentality, potential, culture and social behavior of the community. Therefore, the need and provision of public open space requires a more serious approach to planning and design. This study aims to find out and analyze the characteristics of the need for public open space from the socio-cultural aspect and the extent of the influence of socio-cultural aspects on the use of public open space in Banta-bantaeng Village, Rappocini District, Makassar. This research was carried out in Banta-bantaeng Village, Rappocini District, Makassar with a research period starting from May 2016 to October 2016. The methods used in this study are qualitative descriptive and quantitative descriptive methods. The qualitative descriptive method is used to identify the characteristics of Public Open Space while the quantitative descriptive method is used to describe the influence of socio-cultural aspects on the use of public open space through the calculation of simple mathematical formulas. The results of the analysis of the study show that the availability of public open space in Banta-bantaeng sub-district is still very lacking and does not meet the standards for open space needs based on government regulations. The results of this study also show that the lack of availability of open space has resulted in people taking advantage of existing open space in the form of vacant land owned by private communities, existing environmental roads, open spaces owned by agencies and other vacant lands whose status is unclear. Based on the results of the study, it shows that the people of banta-bantaeng village really need open space, especially open spaces such as sports fields and playgrounds. The results of this research are expected to be inputs for the government and for future research related to public open spaces